Random Graph Models Utilization for Economics Purposes - Panuš, Jan; Dymáková, Andrea (SciTePress - Science and Technology Publications, 2017)
This paper explores the usability of random graph models from the field of social network analysis for selected topics in the field of economic sciences. Specific examples are given in the field of international trade and strategic research as part of international research analysis. At present, there is an increasing need to connect individuals or organizations to increasingly complex networks, and as the complexity of such structures grows, the need for understanding how such structures are created and what they actually mean. The method of random graphs used in the paper serves as an appropriate method for such analysis.
Model náhodného grafu pro ekonomické účely
Keywords: Social networks; international trade; strategy research; Sociální sítě; mezinárodní obchod; strategický výzkum